Cognitive performance during prolonged periods in isolated, confined, and extreme environments. (December 2020) - Connaboy, Christopher; Sinnott, Aaron M.; LaGoy, Alice D.; Krajewski, Kellen T.; Johnson, Caleb D.; Pepping, Gert-Jan; Simpson, Richard J.; Bower, Joanne L.; Alfano, Candice A.
Abstract: Background: Astronauts are required to perform a variety of cognitively demanding tasks in the face of multiple prolonged stressors in isolated, confined and extreme (ICE) environments. Short-term ICE environmental exposure can negatively affect cognitive performance, alter emotional responses, and increase reaction time in affordance-based tasks; however, these domains have not been studied simultaneously in prolonged ICE settings. Coastal and Inland Antarctic stations are excellent analogs for spaceflight based on overlapping environmental features such as limited external communication and confinement in extreme conditions. Our purpose was to investigate the effects of 5-month ICE environment analogs, and co-occurring emotional responses, on cognitive performance and affordance perception. Methods: Participants assigned to either Inland or Coastal stations completed the Psychomotor Vigilance Test (PVT), Spaceflight Cognitive Assessment Tool for Windows (WinSCAT), Perception-Action Coupling Task (PACT), and Mental Health Checklist (MHCL) each month for five consecutive months. A series of 1-way ANOVAs were conducted to evaluate WinSCAT, PVT, and PACT performance across time. A series of backward stepwise linear regressions were conducted to determine if duration of ICE environment exposure (months 1–5), station (Coastal and Inland), gender (male and female), education (college degree and no degree), and time of day, in addition to Positive Adaptation, Poor Self-Regulation, and Anxious Apprehension MHCL subscales, were related to cognitive performance outcomes, including WinSCAT composite, PVT median reaction time and lapses, and PACT accuracy and lapses. Results: A within-subjects' effect indicated improvements across WinSCAT composite score, PACT Accuracy, and PACT lapses. Final regression models were significant across all outcomes, and indicate an improvement in WinSCAT and PACT performance during the winter over, assigned station and education level marginally contributed to the observed variance in cognitive performance. Conclusion: Sustained attention, cognitive performance, and affordance perception and actualization outcomes were marginally affected, or improved, during a prolonged ICE environmental exposure. Highlights: Astronauts must maintain optimal occupational performance during spaceflight. Affordance perception and actualization underlie successful task completion. Prolonged exposure to isolated, confined, and extreme environments can disrupt optimal function. Co-occurring emotional changes may also modulate perceptuo-motor performance.